SIGNIFICANCE OF VALUE CHAIN ANALYSIS FOR CHILLI - THE CASE OF KARNATAKA CHILLI MARKET - SANDEEP K. T*; NAVITHA THIMMAIAH (The Journal of Research ANGRAU, 2020)
Value chain analysis for chilli in Karnataka revealed that fixed costs formed a smaller proportion of the total cost of dry chillies processing (ranging from 13.17% in the case of medium size processing units to16.98% in the case of large units). However, large units had relatively greater proportion of fixed costs as they mechanized most of the stages of processing in order to reap economies of scale. Among the various components of variable costs, raw material (i.e. the dry chillies) accounted for the highest percentage, ranging from 13.39% in respect of large processors to 18.82% in the case of small size processors.In all the three value chains identified, the value addition cost in chain 1 (VAC 1) was the highest with Rs.380 and the lowest is in case of VAC2 with Rs.267. Among the various persons involved in the value chain, the wholesaler and processor played an important role; the former being important in grading, packing and transportation; and the latter being crucial in converting raw chillies into value-added products. The retailer was only involved in the task of moving the produce (raw or processed) to the consumer.